Large mismatch profile predicts rapidly progressing brain edema in acute anterior circulation large vessel occlusion patients undergoing endovascular thrombectomy - Shao, Yanqi; Chen, Xinyi; Wang, Huiyuan; Shang, Yafei; Xu, Jie; Zhang, Jinshi; Wang, Peng; Geng, Yu (Frontiers in Neurology, 2023)
Background Brain edema is a severe complication in patients with large vessel occlusion (LVO) that can reduce the effectiveness of endovascular therapy (EVT). This study aimed to investigate the association of the perfusion profile at baseline computed tomography (CT) perfusion with rapidly progressing brain edema (RPBE) after EVT in patients with acute anterior LVO. Methods We retrospectively reviewed consecutive data collected from 149 patients with anterior LVO who underwent EVT at our center. Brain edema was measured by the swelling score (0–6 score), and RPBE was defined as the swelling score increased by more than 2 scores within 24 h after EVT. We investigated the effect of RPBE on poor outcomes [National Institute of Health Stroke Scale (NIHSS) score and modified Rankin scale (mRS) score at discharge, the occurrence of hemorrhagic transformation, and mortality rate in the hospital] using the Mann–Whitney U-test and chi-square test. A multivariate logistic regression model was used to assess the relationship between perfusion imaging parameters and RPBE occurrence. Results Overall, 39 patients (26.2%) experienced RPBE after EVT. At discharge, RPBE was associated with higher NIHSS scores (Z = 3.52, 95% CI 2.0–12.0, P < 0.001) and higher mRS scores (Z = 3.67, 95% CI 0.0–1.0, P < 0.001) including the more frequent occurrence of hemorrhagic transformation (χ2 = 22.17, 95% CI 0.29–0.59, P < 0.001) and higher mortality rates in hospital (χ2 = 9.54, 95% CI 0.06–0.36, P = 0.002). Univariate analysis showed that intravenous thrombolysis, baseline ischemic core volume, and baseline mismatch ratio correlated with RPBE (all P < 0.05). After dividing the mismatch ratio into quartiles and performing a chi-square test between quartiles, we found that the occurrence of RPBE in Q4 (mismatch ratio > 11.3) was significantly lower than that in Q1 (mismatch ratio ≤ 3.0) (P < 0.05). The result of multivariate logistic regression analysis showed that compared with baseline mismatch ratio <5.1, baseline mismatch ratio between 5.1 and 11.3 (OR:3.85, 95% CI 1.06–14.29, P = 0.040), and mismatch ratio >11.3 (OR:5.26, 95% CI 1.28–20.00, P = 0.021) were independent protective factors for RPBE. Conclusion In patients with anterior circulation LVO stroke undergoing successful EVT, a large mismatch ratio at baseline is a protective factor for RPBE, which is associated with poor outcomes.